Creature of Habit: A self-report measure of habitual routines and automatic tendencies in everyday life. (1st October 2017) - Ersche, Karen D.; Lim, Tsen-Vei; Ward, Laetitia H.E.; Robbins, Trevor W.; Stochl, Jan
Abstract: Our daily lives involve high levels of repetition of activities within similar contexts. We buy the same foods from the same grocery store, cook with the same spices, and typically sit at the same place at the dinner table. However, when questioned about these routine activities, most of us barely remember the details of our actions. Habits are automatically triggered behaviours in which we engage without conscious awareness or deliberate control. Although habits help us to operate efficiently, breaking them requires great effort. We have developed a 27-item questionnaire to measure individual differences in habitual responding in everyday life. The Creature of Habit Scale (COHS) incorporates two aspects of the general concept of habits, namely routine behaviour and automatic responses. Both aspects of habitual behaviour were weakly correlated with underlying anxiety levels, but showed a more substantial difference in relation to goal-oriented motivation. We also observed that experiences of adversity during childhood increased self-reported automaticity, and this effect was further amplified in participants who also reported exposure to stimulant drugs. The COHS is a valid and reliable self-report measure of habits, which may prove useful in a number of contexts where discerning individuals' propensity for habit is beneficial. Highlights: The COHS is a valid and reliable self-report measure of proneness to habits. It assesses two aspects of habits: routine behaviour and automatic responses. The routine subscale is predominated by items favouring regularity and familiarity. The automaticity subscale is predominated by eating-related items.